Functional role of pyruvate kinase M2 in cell cycle arrest and extracellular matrix secretion of renal tubular epithelial cell induced by transforming growth factor-β1 - Wu Hong-luan; An Ning; Chen Xiao-cui; Pang Hao-wen; Yang Chen; Liu Hua-feng (Linchuang shenzangbing zazhi)
Objective To explore the functional role of pyruvate kinase M2（PKM 2） in cell cycle arrest and extracellular matrix secretion of renal tubular epithelial cell induced by transforming growth factor-β1（TGF-β1）.Methods HK-2 cells were stimulated by TGF-β1 for establishing an in vitro model of renal tubulointerstitial fibrosis.The function of dimeric PKM2 was suppressed by a PKM2 allosteric agent TEPP-46 or its antagonist shikonin.The expressions of fibronectin, collagen I and connective tissue growth factor（CTGF） were detected by Western blot.The ratio of HK-2 cells in cycle phase was performed by propidium iodide staining and analyzed by flow cytometry.Also the expression of cell cycle inhibitor p21 was detected by Western blot.Results As compared with control-treated cells, a treatment of TGF-β1 significantly boosted the levels of extracellular matrix fibronectin, collagen I,pro-fibrotic CTGF and dimeric PKM2.By contrast, TEPP-46 or shikonin markedly suppressed the elevations of fibronectin, collagen I and CTGF.Moreover, an inhibition of dimeric PKM2 by TEPP-46 or shikonin remarkably suppressed the proportion of TGF-β1-treated HK-2 cells in G1 phase through a down-regulation of p21.Conclusion Dimeric PKM2 promotes cell cycle arrest and extracellular matrix secretion of renal tubular epithelial cell induced by TGF-β1.And targeting dimeric PKM2 may represent a novel therapeutic strategy for delaying the progression of renal tubulointerstitial fibrosis.